An RFID-based monitoring system for elderly care - Li, Shao Ran (2014)
Wearable computing device is the most prevailing innovations in 2013, and one of the highest demanding are is healthcare market. Relying on the technologies such as body sensor network (BSN) and Real Time Locating System (RTLS), wearable health devices help both patients and clinicians to monitor vital signs and symptoms.